PENGARUH GAYA KEPEMIMPINAN DEKANAT DAN REKTORAT TERHADAP KINERJA PEGAWAI DI UNIVERSITAS IBN KHALDUN BOGOR - Didi Hilman (STIE Binaniaga, 2005)
This study attempted to investigate the relationship between leadership style ofoffice of University Head and leadership style of office of University Head of with employeesperformance of the University of Ibn Khaldun Bogor. This study conducted by survey method. Target population is all employees of the University of Ibn Khaldun Bogor of 32 totally, whice of 29 samples taken randomly.Reseach instrument for leadership style of office of University Head and based on content validity.The mainstay is calculated by alpha cronbach formulation. Tes result indicates that each instrumentmainstay as follows : Instrument of employees performance is rxy = 0.349, leadership style of office ofUniversity Head and office academic affair, respectively 0.304.Quantitatively, data analysis conducted by descriptive statistic and analysis technique of productmoment correlation and regression method.Test result conclude following items: firstly, there is a positive relationship between leadership styleof office of university head ( X1 ) and employees performance (Y) is with significance level is 0.05.secondly, there is positive relationship between leadership of office academic affair (X2) with employeesperformance (Y) is with significance level is 0,05. thirdly, there is positive relationship between leadership style of office of university head and office of academic affair with employees performance simultaneously,viz, with significance level is 0.05.Whereas, variable contribution of leadership style of office of university head with employeesperformance is and variable contribution of leadership style of office of academic affair with employeesperformance is.Kata kunci : gaya kepemimpinan, kinerja pegawai.